Profile of the health network in the extreme south of Santa Catarina: potential and challenges in the implementation of a medical course (Research, Society and Development, 2021)
Strengthening partnerships between health services and universities are fundamental for the consolidation of a health system that is more effective for the population. In this sense, this research aims to understand the structure of the existing health network in the extreme south region of Santa Catarina, relating to the level of complexity of the services offered. Such services are part of the teaching practice scenarios for students of the UFSC Medicine course at the Araranguá campus, which was implemented in 2018 and is in the process of consolidation. A cross-sectional study was carried out in the months of June and July 2020, through the collection of electronic data from DATASUS. The results found showed that, both in Primary Care and in the high and medium complexity, there are few services offered and / or low number of qualified professionals to meet the demand in the Amesc region. It is concluded that the entrance of medical students and, later, of the graduates, in the medium and long term, will result in the strengthening of the local health system.